Intraosseous proliferative sparganosis: a case report and review of the literature - Settakorn J. (2014)
Intraosseous proliferative sparganosis is an extremely rare parasitic disease in which the larvae of incomplete differentiated sparganum proliferate in the human bone. We present the first case of intraosseous proliferative sparganosis arising in the long bone. The patient was a 51-year-old man who complained of a slow growing painful mass on his right leg. The radiographic findings showed an infiltrative osteolytic lesion with speckled calcification at the proximal tibia the clinical diagnosis of which favored chondrosarcoma. Incisional biopsy revealed an innumerable number of small globular shapes, whitish parasites. Histologically, the parasites were composed of a few layers of smooth muscle and several calcerous bodies that were enclosed within a single row of tegumental cells. The latter exhibited a wavy appearance and coated with microvilli. These morphologic findings confirmed the nature of these maldifferentiated larvae. The patient was treated by partial resection of the lesion. This should remind clinicians that parasitic infection of the bone can produce a tumor-like lesion.